Assessing the Use of Animated Video in Improving Pronunciation of Coronal Obstruent Sounds among MAN 2 Palu Students - Hastini; Murkim; Sabang, Rahmad Rizkyanto; Bochari, Siska (Universitas Cokroaminoto Palopo, 2023)
This research aims to determine if YouTube videos can significantly improve the pronunciation of the eleventh-grade students of MAN 2 Kota Palu. It also aims to identify the most difficult sounds to pronounce. This research focuses on segmental features of fricative sounds such as sh/ʃ/, zh/ʒ/, th/θ/, and th/ð/; affricative sounds such as ch/ʧ/ and j/dʒ/. Both quantitative and quasi-experimental research designs were used in this research. The population of this study was the eleventh-grade IPA students of MAN 2 Kota Palu consisting of 163 students. The researchers used purposive sampling and adapted two groups: the eleventh-grade IPA 3 and the eleventh-grade IPA 5 (experimental and control). The oral test was used in this study and divided into two parts (the pre-test and the post-test). To analyze the data, the researchers used SPSS (Statistical Package for Social Sciences) 22. According to the analysis data, videos from YouTube could improve the pronunciation of the eleventh-grade students of MAN 2 Palu City. The experimental groups' average scores were higher than the control group’s (84.77 > 55.88). In addition, the result of sig. (2-tailed) is lower than 0.05. Therefore, it can be concluded that the hypothesis is accepted.